Identification And Sequence Based Detection Of Wssv Infecting Spf Litopeneaus Vannamei (Boone, 1931) In Captivity - M.A.BADHUL HAQ,; N.KAVITHA,; R.VIGNESH,; R. SHALINI, (International Journal of Pharma and Bio Sciences, 2012)
The objective of the present investigation was to determine the level of WSSV transmission from the infected tiger prawn Penaeus monodon to SPF Litopenaeus vannamei in laboratory captivity condition, in connection with to PCR detection and viral genome sequence. The nested PCR product band was ranged between 296 to 910 bp and was found during entire period from the experimental studies of SPF L.vannamei shrimps. WSSV was used as an out group for this phylogeny analysis. The constructed Phylogram showed healthy Inter-specific variations as the clades of other geographical gene were clearly segregated. Nucleotide composition of the test organisms showed average amount of G+C content (~47.0%). G+C content of the WSSV genome were analyzed and there was a little fluctuation in the G+C content of white spot syndrome which differed from the other nucleotide composition of test organism.